Assembly and analysis of the complete mitochondrial genome of the Chinese wild dwarf almond (Prunus tenella) - Liu, Xingyue; Zhang, Dongdong; Yu, Zhenfan; Zeng, Bin (Frontiers in Genetics, 2024)
The wild dwarf almond (Prunus tenella) is one of the national key grade II-protected wild plants in China. It is a relic deciduous forest species from the middle Eocene of the ancient Mediterranean Sea and is also known as a "living fossil of plants." It is distributed in Southeast Europe, West Asia, Central Asia, Siberia, and Xinjiang (Tacheng) and other areas of China. The plant grows on arid slopes, steppes, depressions, and valleys at an altitude of 1200 m. The seeds of wild dwarf almonds are frost resistant and contain oil and bitter lentil glycosides, which possess medicinal value. Additionally, the seeds of wild dwarf almonds can be used as the original material for breeding new varieties of almonds and obtain ornamental flowers and trees.The complete mitochondrial genome of P. tenella was sequenced and assembled using two sequencing platforms, namely Illumina Novaseq6000 and Oxford Nanopore PromethION. The assembled genome was 452,158-bp long with a typical loop structure. The total number of A, T, C, and G bases in the genome was 122,066 (26.99%), 124,114 (27.45%), 103,285 (22.84%), and 102,693 (22.71%), respectively, with a GC content of 45.55%. A total of 63 unique genes, including 36 protein-coding genes, 24 tRNA genes, and 3 rRNA genes, were identified in the genome. Furthermore, codon usage, sequence duplication, RNA editing, and mitochondrial and chloroplast DNA fragment transfer events in the genome were analyzed. A phylogenetic tree was also constructed using 30 protein-coding genes that are common to the mitochondrial genomes of 24 species, which indicated that the genome of wild lentils is highly conserved with those of apples and pears belonging to Rosaceae.Assembly and annotation of the P. tenella mitochondrial genome provided comprehensive information about the mitochondrial genome of wild dwarf almonds, This study provides information on the mitochondrial genome of Prunus species and serves as a reference for further evolutionary studies on wild dwarf almonds.